Environmental physical cues determine the lineage specification of mesenchymal stem cells - Huang, Chao; Dai, Jingxing; Zhang, Xin A. (Biochimica et biophysica acta, 2015)
Physical cues of cellular environment affect cell fate and differentiation. For example, an environment with high stiffness drives mesenchymal stem cells (MSCs) to undergo osteogenic differentiation, while low stiffness leads to lipogenic differentiation. Such effects could be independent of chemical/biochemical inducers. Stiffness and/or topography of cellular environment can control MSC differentiation and fate determination. In addition, physical factors such as tension, which resulted from profound cytoskeleton reorganization during MSC differentiation, affect the gene expression essential for the differentiation. Although physical cues control MSC lineage specification probably by reorganizing and tuning cytoskeleton, the full mechanism is largely unclear. It also remains elusive how physical signals are sensed by cells and transformed into biochemical and biological signals. More importantly, it becomes pivotal to define explicitly the physical cue(s) essential for cell differentiation and fate decision. With a focus on MSC, we present herein current understanding of the interplay between i) physical cue and factors and ii) MSC differentiation and fate determination. Biophysical cues can initiate or strengthen the biochemical signaling for MSC fate determination and differentiation. Physical properties of cellular environment direct the structural adaptation and functional coupling of the cells to their environment. These observations not only open a simple avenue to engineer cell fate in vitro, but also start to reveal the physical elements that regulate and determine cell fate. •Environmental physical cues can determine MSC fate and differentiation.•Cytoskeleton and nuclear skeleton undergo reorganization during MSC differentiation.•MSC fate determination and differentiation are associated with changes in cellular biophysical properties.•Physical cues and chemical inducers specify MSC lineages by regulating cell adhesion molecules and Rho GTPases.